Hungry girl 300 under 300 : 300 breakfast, lunch & dinner dishes under 300 calories - Lillien, Lisa (St. Martin's Griffin, 2011)
"Super-simple, low-calorie, great-tasting meal ideas aren't easy to come by. 300 Under 300 will offer up so many guilt-free breakfast, lunch and dinner dishes, it'll make your head spin! It's meal-mania, HG style! This book features three hundred satisfying and delicious recipes for full on meals, snazzy sides and satisfying snacks that contain less than 300 calories. In addition to traditional Hungry girl recipes, this book will serve up a slew of soon-to-be famous HG triplets: three-ingredient combos that take easy to a whole new level! Included will be... Chicken Carbonara a la Hungry Girl, Kickin' Buttermilk, Faux-Fried Chicken, Jumpin' Jack Chicken with Mashies Platter, Twice-as-Nice Guapo Taco, Crispy-licious Faux-Fried Onion, Frenzy Crock-Pot , Cinna-Apples 'n Oats, Cheesy Pigs in Bacon, Blankies Early-Riser, Pigs in a Blanket Breakfast Scramble, Pizza Pie, Outside-In Turkey Tamale Pie, Purple Pizza Eaters, The Crab Rangoonies, Pizza-bellas ...and more!"--